Perancangan Aplikasi Mobile Android Untuk Laporan Kholas Tilawah - Roro Santi; Komalasari, Rita (LPPM POLITEKNIK LP3I BANDUNG, 2023)
Tilawah is the recitation of verses from the Qur'an, performed continuously with certain reading standards and rules. Communities to maintain this activity can be the right choice. One of the online recitation communities ODOJ (One Day One Juz), is the largest recitation community in Indonesia, which is also crowded with Islamic worshipers from all over the archipelago. This community utilises the WhatsApp (WA) application media, as its communication medium. And ODOJ also uses the WA Group (WAG) feature, which aims to control and record the daily recitation report activities of its members. The bigger a community is, the more data in it, which should need a certain way so that data management can be effective and efficient. The design of android mobile applications is a solution to the problem that aims to provide convenience in doing the data collection. Data collection that aims as an evaluation material for its members from the admin of the WA group. Not as a substitute for WAG, because communication between members must be maintained, but as a convenience for data management, especially the admin. The system development method in this study uses a prototype model.